2016
DOI: 10.1556/032.2016.66.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Discouraged or added worker effect: Which one prevails in the Polish labour market?

Abstract: We test whether the discouraged worker or added worker effect prevails in the Polish labour market. The discouraged worker effect implies that the participation rate is procyclical with respect to the GDP and countercyclical with respect to the unemployment rate. The added worker effect yields contrary findings. We analyse the period 1994–2014 with quarterly data. We focus on the working age population, both males and females. We apply a range of methods to obtain robust results, some of which have never been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…The cycles of the labour force participation rate were slightly longer than the GDP cycles, lasting an average of 4.9 years. These results confirm the previous research of Gałecka-Burdziak and Pater (2016). Other indicators, including unemployment, job search duration, and wages, fluctuated with higher periodicity, of around 10 years.…”
Section: Datasupporting
confidence: 92%
See 2 more Smart Citations
“…The cycles of the labour force participation rate were slightly longer than the GDP cycles, lasting an average of 4.9 years. These results confirm the previous research of Gałecka-Burdziak and Pater (2016). Other indicators, including unemployment, job search duration, and wages, fluctuated with higher periodicity, of around 10 years.…”
Section: Datasupporting
confidence: 92%
“…For example, some studies investigated the determinants of the labour market status and the indicated phenomena (Dagsvik et al, 2006(Dagsvik et al, , 2013van Ham et al, 2001), while others explored the labour supply model at the household level (Baslevent & Onaran, 2003;Bredtmann et al, 2018;Karaoglan & Okten, 2015;Mankart & Oikonomou, 2016;Stephens, 2001) The labour market in Poland has also been studied quite extensively. Gałecka-Burdziak and Pater (2016) found a significant and time-varying added worker effect, as well as a discouraged worker effect for both sexes, for the 1994-2014 period. The AWE was shown to be considerably stronger in recessions than in economic expansions.…”
Section: Literature Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…Del Boca, Locatelli, and Pasqua (2000) and Ghignoni and Verashchagina (2016) have identified the same effect for Italy. Parker and Skoufias (2004) detect empirical evidence of a prevailing AWE in Mexico, and Gałecka‐Burdziak and Pater (2016) do the same for Poland. In the Spanish case, this effect is dominant in Prieto‐Rodríguez and Rodríguez‐Gutiérrez (2000, 2003), and partially in Congregado, Golpe, and Van Stel (2011).…”
Section: Literature Reviewmentioning
confidence: 93%
“…Additionally, low wages discourage individuals from taking up a job, especially if they are aware of state assistance, when the incentives to take up a job may be weakened by the discouraged worker effect (Gałecka-Burdziak -Pater 2016). Low wages may lead to the expansion of informal or parallel job markets.…”
Section: Introductionmentioning
confidence: 99%